Cation export by overland flow in a recently burnt forest area in north-central Portugal - Machado, A. I.
The current fire regime in the Mediterranean Basin constitutes a serious threat to natural ecosystems because it drastically enhances surface runoff and soil erosion in the affected areas. Besides soil particles themselves, soil cations can be lost by fire-enhanced overland flow, increasing the risk of fertility loss of the typically shallow and nutrient poor Mediterranean soils. Although the importance of cations for land-use sustainability is widely recognized, cation losses by post-fire runoff have received little research attention. The present study aimed to address this research gap by assessing total exports of Na+, K+, Ca2+ and Mg2+ in a recently burnt forest area in north-central Portugal. These exports were compared for two types of planted forest (eucalypt vs. maritime pine plantations), two types of parent materials (schist vs. granite) and for two spatial scales (micro-plot vs. hill slope). The study sites were a eucalypt plantation on granite (BEG), a eucalypt plantation on schist (BES) and a maritime pine plantation on schist (BPS). Overland flow sampleswere collected during the first sixmonths after the wildfire. Cation losses differed strikingly between the two forest types on schist, being higher at the eucalypt than pine site. This differencewas evident at both spatial scales, and probably due to the extensive cover of a needle cast fromthe scorched pine crowns. The role of parentmaterial in cation exportwas less straightforward as it variedwith spatial scale. Cation losseswere higher for the eucalypt plantation on schist than for that on granite at the micro-plot scale, whereas the reverse was observed at the hill slope scale. Finally, cation yields were higher at the micro-plot than slope scale, in agreement with the general notion of scaling-effect in runoff generation.